Optimising the energy performance of the residential stock of the Kingdom of Saudi Arabia by retrofit measures - Alosaimi, Azzam (2023)
Building energy demands and green house gases are raising and a variety of energy efficiency frameworks, legislation, and housing approvals have evolved worldwide. The KSA is one of the largest energy producers and consumers internationally, with the residential sector using 52% of total energy generation. The KSA government has begun energy efficiency initiatives and policies that intend to reduce the residential energy demands via a series of regulations including Vision 2030 and the KSA building code. The regulations aim to assess the energy performance of residential buildings in order to lower the energy demands and greenhouse gas emissions to meet international carbon emissions requirements. The KSA targets to generate 9.5 GW from renewable energy by 2023, and 58.7 GW by 2030, which accounts for about 30% of the total energy generation capacity. Research has shown that in order to effectively reduce the energy demands and achieve worldwide carbon emissions targets, large-scale implementation interventions are required.